2022
DOI: 10.1002/lio2.949
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events of coblation or microdebrider in pediatric adenoidectomy: A retrospective analysis in 468 patients

Abstract: Objective: Childhood obstructive sleep apnea hypopnea syndrome (OSAHS) is a common clinical disease that can cause serious complications if not treated in time.Adenoidectomy with or without tonsillectomy is the most important first line surgical treatment of obstructive sleep apnea in children. The aim of this study was to compare the differences between these two surgical procedures for adenoidectomy in terms of operation time, intraoperative blood loss, proportion of patients experiencing postoperative delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The most remarkable is that it may impair the presence of enough tissue to perform histology assessment. In fact, despite the evidence is scarce, some authors have suggested that some secondary effects are more prone to occur with the coblation than microdebrider [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most remarkable is that it may impair the presence of enough tissue to perform histology assessment. In fact, despite the evidence is scarce, some authors have suggested that some secondary effects are more prone to occur with the coblation than microdebrider [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing postoperative pain, reducing the operative and haemostasis duration, and minimising intraoperative and postoperative haemorrhage risk have brought attention to new surgical techniques and instrumentation. Different techniques are nowadays used for paediatric adenoidectomy: cold surgery—the conventional curettage (so-called blind curettage) with Beckmann curette; microdebrider (shaver) or endoscopic—assisted adenoidectomy; hot methods—electrocautery adenoidectomy [ 3 , 4 ], adenoidectomy with radiofrequency (coblation) [ 3 , 4 ], each method presenting its own advantages and possible side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors agree that operative time and blood loss are significantly reduced in the case of electrocautery used in adenoidectomy surgery [ 5 , 6 , 7 , 8 ]. Whereas some authors report no complications after electrocautery adenoidectomy [ 9 , 10 ], others report a higher risk of secondary (delayed) haemorrhage and a greater incidence of neck pain (referred pain at the back of the child’s head) after bipolar electrocautery use (incidence up to 12%) [ 2 , 4 , 5 , 11 ], prolonged nasal obstruction, and velopharyngeal insufficiency symptoms.…”
Section: Introductionmentioning
confidence: 99%